Removal of Pharmaceutical (Paracetamol) by using CNT/ TiO2 Nanoparticles - Aseel M. Aljeboree (Journal of Global Pharma Technology, 2016)
Paracetamol has been the highly usage drug in the world which increased environmental pollution, it has been effected in human life, flora and fauna in the world. Adsorption technique was used to remove paracetamol from water using CNT/TiO2 nanoparticles; the TiO2 was developed from CNT/TiO2 nanoparticles. The experiments were carried out to drug uptake by CNT/TiO2 nanoparticles and effect of some experimental factors like temperature, initial drug concentration, adsorbent dosage, , and particle size in solution, also the adsorption equilibrium was characterized using Langmuir and Freundlich isotherm models. The results have shown immense potential, it was found that correlation coefficient value deal with of the drug, while Langmuir equation was found a good correlation of drug.Keywords: Adsorption, Pharmaceutical, Paracetamol, TiO2, Isotherm models, CNT.